Analysis of Debt Negotiation of PT. Garuda Indonesia Through “ICON” Negotiation Model - Muhammad Dede Puja Kusuma; Pratiwi, Tiffany Setyo (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
This paper will discuss the debt negotiation of PT. Garuda Indonesia. PT. Garuda Indonesia has been declared bankrupt at least three times. The first was in 1968, the second in 1998, and the third in 2021. This study will focus on negotiates debt of PT. Garuda Indonesia with lessors and creditors in 2021. In September 2021, Garuda Indonesia was threatened with bankruptcy with a recorded $9.75 billion or equivalent to Rp138.93 trillion. As the only state-owned air transportation service company, the Ministry of State-Owned Enterprises (BUMN) decided negotiates with lessors and creditors. This study will use a qualitative method with secondary data from literature studies. This study will use “ICON” model negotiation models to analyze PT Garuda Indonesia’s debt negotiations. “ICON” is four interrelated elements, namely Interests, Criteria, Choices, and Alternatives Without Agreement, which help prepare negotiations so that it is expected to provide a greater chance of success in negotiations. This study finds that the accuracy interest of PT. Garuda Indonesia is the restructuring of the application or Postponement of Debt Payment Obligations (PKPU). The most sensible option with the Suspension of Debt Payment Obligations (PKPU) negotiation in court chosen by Garuda. Then, the criteria standard is from the regulation has been stated in Article 222 paragraph (3) of Law Number 37 of 2004 become a fair process to each party by law. Lastly, the Non-Agreement Alternative are conducting a merger, liquidation, or state capital participation if homologation PKPU is not achieved. From the results of this negotiation process, all parties agreed to accept the debt restructuring peace proposal and Garuda avoided bankruptcy. The total votes that approved the peace plan represented 97.46% of the votes.